2020
DOI: 10.2147/dddt.s255828
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exosomes Derived from MicroRNA-146a-5p-Enriched Bone Marrow Mesenchymal Stem Cells Alleviate Intracerebral Hemorrhage by Inhibiting Neuronal Apoptosis and Microglial M1 Polarization</p>

Abstract: Introduction: Intracerebral hemorrhage (ICH) is a devastating type of stroke with high mortality, and the effective therapies for ICH remain to be explored. Exosomes (Exos) have been found to play important roles in cell communication by transferring molecules, including microRNAs (miRNAs/ miRs). MiRNAs are critical regulators of genes involved in many various biological processes and have been demonstrated to aggravate or alleviate brain damages induced by ICH. The aim of the present study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 46 publications
(59 reference statements)
2
69
0
1
Order By: Relevance
“…Studies have determined that the level of SOD in patients with cerebral hemorrhage (113.62 ± 9.14 U/mL) is significantly lower than healthy (161.20 ± 21.12 U/mL) [ 65 ]. It is a common indicator for evaluating oxidative stress in mouse models of ICH [ 2 , 6 , 56 , 58 , 66 , 67 ].…”
Section: Markers For Detecting Os After Ichmentioning
confidence: 99%
“…Studies have determined that the level of SOD in patients with cerebral hemorrhage (113.62 ± 9.14 U/mL) is significantly lower than healthy (161.20 ± 21.12 U/mL) [ 65 ]. It is a common indicator for evaluating oxidative stress in mouse models of ICH [ 2 , 6 , 56 , 58 , 66 , 67 ].…”
Section: Markers For Detecting Os After Ichmentioning
confidence: 99%
“…Recently, treatment strategies based on exosomes of MSCs have been widely reported in many diseases. The potential mechanism of exosomes treatment in the ICH mainly comprises the anti-apoptotic, neurogenesis, angiogenesis, and anti-inflammation effects through its miRNAs ( Cai et al, 2020 ; Duan et al, 2020 ).…”
Section: Potential Strategies For Mscs Treatment Enhancement After Icmentioning
confidence: 99%
“…Research in models of cutaneous wound-healing and spinal cord ischemiareperfusion injury (SCIRI) have also shown that BMMSC-EV induced macrophage M2 polarization was associated with the AK2-STAT6 signaling pathway (Sun et al, 2018), miR-223 (He et al, 2019), and miR-124-3p/Ern1 (Li et al, 2020). BMMSCderived EVs also inhibited M1 microglia activation and tissue neutrophil infiltration and reduced the expression of TNF-α, IL-1β, and IL-6 in a rat ICH model (Duan et al, 2020). Similarly, ADMSC-EV treatment in a murine model of LPS-induced lung injury mitigated injury, increased localized expression of miR-27a-3p, and induced M2 macrophage polarization via NFKB1 signaling .…”
Section: Effects On Macrophage Polarizationmentioning
confidence: 98%